Удосконалення системи управління якістю підприємств – виробників будівельних матеріалів - Двуліт, З. П.; Ільницька, К. О.; Завербний, А. С.; Передало, Х. С.; Dvulit, Z. P.; K. O. Ilnytska.; Zaverbnyj, A. S.; Peredalo, K. S. (Видавництво Львівської політехніки, 2020)
Розглянуто проблему необхідності запровадження та моніторингу системи управління якістю на прикладі галузі виробництва будівельних матеріалів. Проаналізовано ринок обсягів виробництва будівельних матеріалів у 2013–2018 рр., суб’єктів господарювання у галузі виготовлення виробів із цегли та підприємства у галузі будівельних матеріалів за 2010–2018 рр. Розвинено алгоритм виконання процесу контролювання засобів моніторингу та вимірювального устаткування.

The article describes the importance of implementing and monitoring a quality management system based on the example of the building materials industry. A concise analysis of the market according to the recent years’ indicators was conducted, which highlights the industry importance in the domestic economy. Among the qualitative factors affecting competitiveness, the main tool is the production quality management system. The quality of the products requires constant monitoring, both internal and external. With the advancement of scientific and technological progress, it is expedient in part and quality management to constantly improve the forms and methods of control in order to increase its efficiency. The essence of realization of control of the quality management system and its monitoring means was investigated. The flowchart of the implementation process for the above measures is proposed. The literature sources in the field of QMS by sectors were reviewed, insufficiently researched directions were identified, and the prospects for further investigation in this direction were formulated. The investigation of the building materials production field was carried out, the analysis of the market by volume of sold products for 2013–2018 was realized; the number of enterprises in the industry and their shares in all economic entities of Ukraine for 2010–2018 was determined. A mechanism for the effective implementation of QMS control was developed in accordance with the requirements, at all stages of its formation and operation. This proposed mechanism allows to improve the system of functioning of the general management over the implementation of the QMS process at the building materials manufacturing company, provides an uninterrupted metrological process and improves the communication between the responsible persons, who analyze the data on monitoring of the measuring equipment.
Improvement of the quality management system for the building materials production enterprises
Keywords: управління; контролювання; моніторинг; система управління якістю; підприємства-виробники будівельних матеріалів; management; control; monitoring; quality management system; manufacturers of building materials; 69.691; 658.5.012.7; 65.018